2011
DOI: 10.1590/s0102-86502011000100006
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effect of 470 nm LED (Light Emitting Diode) in keloid fibroblasts

Abstract: Purpose:To quantify keloid fibroblasts after irradiation with 470nm blue LED, in vitro. Methods: Fibroblasts from keloid and adjacent skin have been obtained from 6 patients. Cells have been cultivated and maintained in DMEM culture medium. In Petri dishes, they were irradiated with energy doses of 6J, 12J and 18J. After 24 h, counting was done by the average of the triplicates for each sample. Results: There were no significant differences in the number of irradiated keloid fibroblasts at the studied doses (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Opländer et al14 demonstrated that single irradiation with 410 or 420 nm LED at 5~10 J/cm 2 inhibits the proliferation of dermal fibroblasts. Bonatti et al15 also reported a significant reduction in the number of normal fibroblasts irradiated with 470 nm light at 18 J/cm 2 . According to Seo et al16, red (630 nm, 9.5 J/cm 2 ) and green (530 nm, 9.8 J/cm 2 ) LED-irradiated cells were significantly more proliferated than cells irradiated with blue light (460 nm, 27 J/cm 2 ).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Opländer et al14 demonstrated that single irradiation with 410 or 420 nm LED at 5~10 J/cm 2 inhibits the proliferation of dermal fibroblasts. Bonatti et al15 also reported a significant reduction in the number of normal fibroblasts irradiated with 470 nm light at 18 J/cm 2 . According to Seo et al16, red (630 nm, 9.5 J/cm 2 ) and green (530 nm, 9.8 J/cm 2 ) LED-irradiated cells were significantly more proliferated than cells irradiated with blue light (460 nm, 27 J/cm 2 ).…”
Section: Discussionmentioning
confidence: 91%
“…Bonatti et al15 showed that a single irradiation with 470 nm LED at 6, 12, and 18 J/cm 2 does not induce significant differences in the number of keloid fibroblasts. To our knowledge, no study reports that LLLT affects the molecules investigated here in keloid fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the skin exposure to blue light results in antibacterial [ 38 40 ], antimicrobial [ 36 , 41 ], and anti-inflammatory [ 42 ] effects. The side effects of blue-light therapy of neonates [ 43 ], suppression of dendritic cell activation [ 44 ] and effect on human dermal fibroblasts [ 45 , 46 ] were also reported. The toxic effect of blue light on the skin was shown to be related to the generation of nonenzymatic nitric oxide (NO) radicals [ 47 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the sequential use of red light PBM in the early phase of wound healing and blue light PBM in the later tissue remodeling phase might help to both quicken wound closure and reduce/prevent subsequent fibrosis or wound contracture. In pathological fibrotic lesions, such as keloid, blue PBM might also tilt the balance toward resolution of fibrosis . One important note is that, through the hydroxyproline assay two days after irradiation, Masson‐Meyers et al suggested that blue light PBM does not reduce collagen synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that blue light PBM may decrease fibroblast activity in vitro , which provides a valuable perspective for anti‐fibrosis treatment. Over‐accumulation of extracellular matrix (ECM) and fibrosis in solid organs such as the lung, kidney, and liver compromises normal physiological functions .…”
Section: Introductionmentioning
confidence: 99%